Successful whole-blood exchange transfusion in a patient with paroxysmal nocturnal hemoglobinuria: A case report and literature review - Zhang, Zhimin (J Int Med Res, 2019)
OBJECTIVE: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare acquired clonal disorder of the hematopoietic stem cells that involves all blood cells. The primary aim of this study was to assess the role of whole-blood exchange (WBE) in treating patients with PNH. METHODS: A 32-year-old male patient was admitted our hospital because of severe anemia. His clinical test results indicated serious hemolysis, with positive anti-I on pretransfusion antibody screening tests. Because immunosuppressive therapy was ineffective and red blood cell (RBC) transfusion may aggravate hemolytic symptoms, the COBE Spectra blood cell separator was used for WBE. RESULTS: We performed WBE, where 1789 mL of the patient’s blood was removed and replaced with 12 U of packed RBCs, along with 150 mL of frozen plasma and 200 mL of normal saline (total volume, 1883 mL), representing an exchange of 42.5% of the patient’s total blood volume (approximately 4209 mL). The WBE treatment was considered successful. Rapid improvement in clinical signs and symptoms were observed after the WBE transfusion. The patient was discharged from the hospital on the third day after treatment. CONCLUSION: Whole-blood exchange may be an applicable emergency treatment for rescuing PNH patients with severe or life-threatening hemolysis.